Zeravschania sola (Apiaceae), a new species from Mazandaran Province, Northern Iran - Lyskov, Dmitry; Zarre, Shahin; Terentieva, Elena; Samigullin, Tahir; Kljuykov, Eugene (Phytotaxa, 2022)
A new species, Zeravschania sola (Apiaceae), is described from the Mazandaran Province, Northern Iran. The new species is recognized by molecular phylogenetic analysis of nrITS as closely related to Z. khorasanica and Z. minjanensis. At the same time, it differs from the above-mentioned species in the stem height and diameter at the base, shape of sheaths, leaf blades size, primary and terminal segments of leaves, and umbel size.